Simulasi Jaringan untuk Sistem Terdistribusi Axigen dengan GNS3 - Shareen Stephanie; Fransiskus Dharma Hadi Wijaya; Given Putra; Surya Dharma Kang; Ferarry Wijaya (Fakultas Teknologi Informasi Universitas Tarumanagara, 2024)
An email server is a program responsible for managing the process of distributing receipts and sending emails. Simply put, an email server manages the process of sending and receiving emails. This simulation was carried out using GNS3. In this simulation there are also components such as routers, switches, firewalls and 3 zone sections, namely inside there are 2 PCs, dmz which has 2 servers, namely mail server and web server and outside zone there is 1 PC to access the web server (web client). The simulation results show that users in the inside and dmz zone have internet connectivity and can access it. Also, users from outside the zone managed to access the Apache HTTP server and CyberPanel server.